The Role of Psycholinguistics in Developing Arabic Language Learning Methods: A Literature Review - Adinda, Dea; Fazira, Era; Abi Hidayah, Fadhla; Nasution, Sahkholid (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2024)
Arabic language learning often experiences obstacles, especially in understanding how students’ cognitive and affective aspects affect their ability to acquire, produce, and understand the language. This indicates the need to apply a multidisciplinary approach that can overcome these challenges. This study aims to examine the role of psycholinguistics in the development of Arabic language learning methods, focusing on students’ cognitive and affective aspects. The research approach used is Systematic Review (SR), by analyzing relevant articles from journals indexed through Google Scholar. The results of the study indicate that the application of psycholinguistics plays a crucial role in the development of Arabic language learning by understanding students’ learning processes and designing appropriate curricula and methods. Approaches such as Task-Based Learning (TBL), Problem-Based Learning (PBL), and Generative Transformative help create more active, communicative, and applicable learning according to students’ needs. In addition, linguistic theories such as structuralism, transformative-generative, and psycholinguistic-based balaghah enable more effective and relevant Arabic language teaching to students’ characteristics and cognitive development.